2022
DOI: 10.1371/journal.pone.0268517
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-patient relationship for multi-period home health care routing and scheduling problem

Abstract: This article proposes a novel dynamic objective function in a multi-period home health care (HHC) problem, known as the nurse-patient relationship (NPR). The nurse-patient relationship score indicating the trust a patient has for his or her care worker increases when the same people meet regularly and decreases when they are apart. Managing human resources in HHC is a combination of routing and scheduling problems. Due to computational complexity of the HHC problem, a 28-day home health care problem is decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Participants emphasized that in addition to learning how to prevent falls, they were able to socialize and establish a close bond with the interventionist in charge of the follow-up. This coincides with other studies which indicate that the trust a patient has in their caregiver increases when the same people meet regularly ( Krityakierne et al, 2022 ). Likewise, when the professional-user relationship is established on the basis of essential attributes such as empathy, presence, contact, authenticity, trust and reciprocity ( Allande-Cussó et al, 2022 ), the quality of care and the satisfaction of both parties improves ( Molina-Mula & Gallo-estrada, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Participants emphasized that in addition to learning how to prevent falls, they were able to socialize and establish a close bond with the interventionist in charge of the follow-up. This coincides with other studies which indicate that the trust a patient has in their caregiver increases when the same people meet regularly ( Krityakierne et al, 2022 ). Likewise, when the professional-user relationship is established on the basis of essential attributes such as empathy, presence, contact, authenticity, trust and reciprocity ( Allande-Cussó et al, 2022 ), the quality of care and the satisfaction of both parties improves ( Molina-Mula & Gallo-estrada, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Sajadi and Ahmadi [31] combined GA with vibration damping optimization (VDO) to optimize the inventory management of perishable products. Krityakierne et al [32] used TS to optimize home healthcare routing and scheduling. There are several reasons for this circumstance.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for a therapeutic relationship to occur, there needs to be genuine empathy that allows for approachability, availability for a beneficial presence and engagement among the parties that reflects respect and trust to allow for the achievement of progress toward care outcomes [17] . Scholars have studied the nature of the nurse-patient relationship among psychiatric nurses [14,17] , home health care [18] , accident and emergency departments [19] and general nursing practice [16] . From these studies, it can be concluded that therapeutic relationships support both patient's psychological and physical needs.…”
Section: The Findings From the Review 51 Therapeutic Nurse-patient Re...mentioning
confidence: 99%